Strategies Employed by Teachers in Forming Groups to Facilitate Group Learning in Selected Primary Schools in Uganda - Geria, Gloria; Opit, Elizabeth; Asiimwe, Joyce Ayikoru (East African Journal of Education Studies, 2025)
This study explores the strategies used by teachers to form groups that facilitate effective group learning in primary schools in Uganda, guided by Vygotsky’s Social Constructivist Theory, Bandura’s Social Learning Theory, and Piaget’s Constructivist Theory. A qualitative exploratory case study design was employed, utilizing interviews, focus group discussions (FGDs), lesson observations, and lesson plan analyses to gather comprehensive insights from both government-aided and private primary schools. Findings indicate that teachers predominantly employ mixed-ability, size-oriented, and random group formation strategies to enhance collaboration and accommodate diverse learner needs. However, the study identified significant gaps in teachers' skills for structuring group activities, particularly in aligning group composition with cognitive, social, and affective learning objectives. The lack of standardized guidelines and adequate training on effective group formation strategies emerged as a barrier, limiting the full potential of group learning pedagogy. The study contributes to educational pedagogy by highlighting the contextual factors influencing group formation strategies in Ugandan primary schools, revealing disparities between teacher practices and optimal group learning conditions. It emphasizes the need for targeted professional development programs to enhance teachers' competencies in group facilitation, alongside increased investment in instructional resources to support structured group activities. Recommendations include implementing comprehensive training on cooperative learning techniques, developing standardized guidelines for group formation, and promoting flexible classroom arrangements to support interactive learning. Future research should explore the long-term impacts of group formation strategies on both academic performance and social skill development, assess the effectiveness of various grouping methods across diverse educational contexts, and examine the role of cultural factors in shaping group learning dynamics. Addressing these gaps will inform evidence-based practices and policy decisions aimed at optimizing group learning pedagogy in primary education.